“It’s the last resort’’ forensic mental health nurses experience on the use of seclusion; implications for use and elimination in clinical practice - Tulloch, Lindsay (The journal of forensic psychiatry & psychology, 2022)
Seclusion is one of the extreme measures of managing violence and aggression. Despite the evidence base for the effectiveness and therapeutic value of seclusion being limited, there arguably remains a compelling case for its use. This qualitative study aimed to explore forensic nurse’s experiences and perspective on the use of seclusion in clinical practice and establish: •What are the factors that influence and inhibit the use of seclusion? •What skills are required when caring for patients in seclusion? A purposive sample of 12 registered and non-registered nurses from a UK high-security hospital consented to engage in a focus group. Thematic analysis was used to interrogate the data. The results included two emerging themes: ‘Keeping everyone safe’ and ‘The challenges’, including the identification of binary oppositions. A rationale for the use of seclusion; it’s a last resort. Evidence of challenges to the therapeutic relationship and communication barriers. Findings illustrate the need to critically examine the practise of seclusion, accuracy of risk assessment, also to balance safety and security proportionately and ensure therapeutic value. The use of a daily dynamic risk assessment and staff relational training is recommended to improve communication and reduce excessive and prolonged use of seclusion